2014
DOI: 10.1002/ece3.1006
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term field experiment of soil transplantation demonstrating the role of contemporary geographic separation in shaping soil microbial community structure

Abstract: The spatial patterns of microbial communities are largely determined by the combined effects of historical contingencies and contemporary environmental disturbances, but their relative importance remains poorly understood. Empirical biogeographic data currently available are mostly based on the traditional method of observational survey, which typically involves comparing indigenous microbial communities across spatial scales. Here, we report a long-term soil transplantation experiment, whereby the same two so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…The difference between any two locations continuously increased with time, which implied that the group of microbes exposed to dramatic climate change is neither resistant nor resilient during the years of the study. Recovery may fail to occur after persistent disturbances caused by climate change, which was demonstrated in a previous study wherein the transplanted soil microbial community was closer to the microbial community in the local soil than that in the original location twenty years after soil transplantation ( Sun et al , 2014 ). In addition, previous studies indicated that the presence of plants may enhance the resilience of soil microbial communities ( de Vries et al , 2012 ) or even inhibit the effects of soil transplantation ( Liu et al , 2014 ), which might be related to the high resource availability offered by the plant ( de Vries and Shade, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The difference between any two locations continuously increased with time, which implied that the group of microbes exposed to dramatic climate change is neither resistant nor resilient during the years of the study. Recovery may fail to occur after persistent disturbances caused by climate change, which was demonstrated in a previous study wherein the transplanted soil microbial community was closer to the microbial community in the local soil than that in the original location twenty years after soil transplantation ( Sun et al , 2014 ). In addition, previous studies indicated that the presence of plants may enhance the resilience of soil microbial communities ( de Vries et al , 2012 ) or even inhibit the effects of soil transplantation ( Liu et al , 2014 ), which might be related to the high resource availability offered by the plant ( de Vries and Shade, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…The transplantation of soils between different geoclimatic regions provides a powerful approach to test the responses of microbial communities to climate change scenarios that simultaneously alter multiple factors ( Bottomley et al 2006 ; Waldrop and Firestone, 2006 ; St John et al , 2011 ; Vanhala et al , 2011 ; Zumsteg et al , 2013 ; Sun et al , 2014 ; Zhao et al , 2014 ). In general, an increase in temperature and precipitation is expected in southward transplantation (climate warming), whereas a decrease in these parameters is expected in northward transplantation (climate cooling) at northern latitudes along the coastal areas.…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbial diversity is critical to the integrity, function, and long-term sustainability of soil ecosystems (Kennedy and Smith 1995). Species diversity indices are important measures of microbial community and are determined by a combination of both historical and contemporary effects (Martiny et al 2006;Sun et al 2014). Increasingly, research suggests that greater species diversity is associated with greater ecosystem stability (McNaughton 1994); therefore, the maintenance and restoration of microbial biodiversity is becoming a key issue in sustainable agricultural systems (Zhao et al 2014).…”
Section: Bacterial Community Composition and Diversitymentioning
confidence: 99%
“…Species composition and diversity index are two important measures of a microbial community, and they are determined by a combination of both historical and contemporary effects (Martiny et al, 2006;Sun et al, 2014). Previous studies revealed that chemical fertilization causes significant changes of the structural composition of bacterial community, but the levels of bacterial diversity remain unaltered in short-term treatments of less than a few years (Wakelin et al, 2007;Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%